Characteristics of Implementation of Distance Remote Access to Learning in Russian Universities - Barakhsanova, Elizaveta Afanasevna (2020)
The purpose of the study is to identify the characteristics of implementation of remote access to learning at university basing on distance learning technology. The basic methods for the relevant problem studying are pedagogical experiment, expert assessment methods, and statistical processing of quantitative results of the research. The experiment involves the students and professors of the Ammosov North-Eastern Federal University (NEFU), the Herzen State Pedagogical University of Russia (RSPU) and Chelyabinsk State University (CSU). The promising areas of distance learning and its effectiveness have been analyzed and generalized. In addition, factors and conditions for providing quick access to the Internet for the educational process have been identified. The substantive aspect of the implementation of remote access to learning in terms of the Major Professional Educational Programs (MPEP) in the field of Pedagogical Education is examined in order to identify their relevance to the distance learning implementation at university. The most widespread digital services have been studied in addition to their effectiveness for the development of training materials that provide educational opportunities of distance learning in terms of the implementation of remote access to learning. The significance of the implementation of distance remote learning for future teachers training at universities is determined. The results of the study prove the necessity to develop educational and methodological materials for the implementation of new form of training in NEFU, RSPU and CSU.